Lost in outer space : the incredible journey of Apollo 13 - Olson, Tod (Olson, Tod. Lost., 2017)
"April 13, 1970: Two hundred thousand miles from Earth and counting, an explosion rips through Jim Lovell's spacecraft. The crippled ship hurtles toward the moon at three times the speed of sound, losing power and leaking oxygen into space. Lovell and hiscrew were two days from the dream of a lifetime - walking on the surface of moon. Now, they will count themselves lucky to set foot on Earth again. From "Houston, we've had a problem" to the final tense moments at Mission Control, Lost in Outer Space takes readers on the unbelievable journey of Apollo 13 and inside the minds of its famous and heroic astronauts. Complete with photographs of the crew and diagrams of the spacecraft, this is an up-close-and-personal look at one of the most thrilling survivalstories of all time"--